Carbonate rocks of west Slovenia as potential sources for hydrocarbons - Ogorelec, Bojan; Jurkovšek, Bogdan; Šatara, Drago; Barić, Gertrud; Jelen, Bogomir; Kapović, Borislav (Geologija, 1996)
The research comprises depositional evironment and lithological characteristics as well as geochemical and optical analyses of 196 limestone and dolomite samples from Upper Permian to Paleocene age from the western part of Slovenian Dinarides. The obtained results of 14 investigated formations are orientational. Triassic and Jurassic rocks contain 0.2 % Corg in average and are not potential source rocks for hydrocarbons. The Upper Permian and Carnian beds contain more Corg, but vitrinite constituent of terrestrial origin is unfavorable for the kerogene composition. The black Lower Cretaceous limestone of lagoonal facies from Trnovo near Nova Gorica can be considered as partial potential source rock for hydrocarbons. Black platy and laminated Komen and Tomaj limestone and rocks of the Liburnian Formation indicate a moderate content of Corg but have unfavorable composition of kerogene.